Theory and Practice for Outdoor Spaces of Urban Challenges: An Environmental Sustainable Design - Kadhum, Lina Kifah; Taki Ali Almusawi, Tahrir; Fadhel Muhkaber Alomari, Ashwaq; Ajeel, Awadh; Qahtan Abd Alrazzaq Alkhayat, Zainab; Nuaman Andagani, Luai (Journal of Engineering and Sustainable Development, 2026)
This article explores the idea of living in outdoor environmental design. It works to highlight the necessity of creating outdoor spaces that will simultaneously create positive physical and mental health effects while observing sustainable environmental practices that increase quality of life. In addition, it emphasizes the role such ideas can have in spreading environmental consciousness through society.  The findings of the research may constitute a theoretical guidance to promote sustainable process design, but their implementation at the local scale is still scarce. In this paper, we examine how local government and community-based organizations are beginning to adopt standards for sustainable environmental design. It highlights the importance of climate-conscious, practice-based, and site-specific outdoor living design in global and local contexts as an effective means to advance environmentally sustainable design through best practices. The described work in this paper also proves, however, that the Sustainable-Based Design approach with local context intelligence can directly contribute to the change of social, economic, and environmental conditions. Findings underscore the importance of community-based approaches for minimising social and psychological fallout from wars, terrorism, and pandemics that interrupt behaviour patterns and collective identity.